Case Report: Simultaneous hepatic and renal echinococcosis in a child: a multidisciplinary approach - Zhou, Quanyu; Xia, Yuxiao; Zou, Haibo (Frontiers in Pediatrics, 2025)
IntroductionEchinococcosis caused by Echinococcus granulosus is a significant public health issue, particularly in pastoral regions. This zoonotic disease is globally distributed and most prevalent in areas with frequent human-livestock interactions. The liver is the most commonly affected organ, followed by the lungs. In children, simultaneous involvement of multiple organs is rare due to immature immune systems and smaller organ sizes. This case highlights the rarity and complexity of simultaneous hepatic and renal echinococcosis in a child.MethodsA 5-year-old boy from a pastoral region in Tibet, China, was admitted due to a palpable abdominal mass detected one month prior. Imaging studies, including CT, identified multiple echinococcal lesions in the liver and a large cystic mass in the kidney. Serological assays confirmed Echinococcus granulosus infection. A multidisciplinary team (MDT) discussion involving pediatricians, anesthesiologists, urologists, and infectious disease specialists developed a tailored surgical plan.ResultsThe patient underwent radical multiple pericystectomies of the liver and endocystectomy of the right renal echinococcal cyst. Intraoperatively, multiple firm, translucent masses in the liver and a large cystic mass in the right kidney were found, both confirmed to be infected with Echinococcus granulosus. Postoperatively, transient hypernatremia and hepatic dysfunction occurred but were effectively managed. The patient was discharged on postoperative day 7 and showed no recurrence at the 1-month follow-up.DiscussionThis case underscores the complexity and rarity of simultaneous hepatic and renal echinococcosis in children. Early diagnosis through detailed medical history, imaging studies, and serological assays is crucial. The multidisciplinary approach, including tailored surgical strategies and postoperative management, was essential for a favorable outcome. The success of pericystectomy highlights the importance of organ-sparing techniques in pediatric patients. However, potential complications like transient hypernatremia emphasize the need for vigilant postoperative monitoring and supportive care. Future research should focus on improving diagnostic precision, surgical methodologies, and postoperative care in children.